2007
DOI: 10.3748/wjg.v13.i11.1646
|View full text |Cite
|
Sign up to set email alerts
|

Role of computed tomographic colonoscopy of postoperative surveillance in patient with gastric cancer

Abstract: AIM:To examine the diagnostic yield of colorectal neoplasia at computed tomographic colonoscopy (CTC) as well as the feasibility of contrast enhanced CTC in patients with gastric cancer. METHODS:To examine the incidence of colon polyp we selected postoperative 188 gastric cancer patients, which we refer to as the 'colon polyp survey group'. To examine the feasibility of CTC for early detection of colon cancer or advanced colon adenoma, we selected 47 gastric cancer patients (M:F 29:18, mean age 53.8 years), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
0
2
Order By: Relevance
“…Most secondary colorectal cancers develop within 3 years of the initial diagnosis, and, since a portion of them steadily develop for 5 years after detection of primary gastric cancer [4,6], screening FCS should be performed for at least 5 years after endoscopic removal of gastric lesions. Meanwhile, the prevalence of overall colorectal polyps and of colorectal adenocarcinomas seen in this study is higher than that observed by previous studies which dealt with the prevalence of colorectal neoplasms in patients with gastric cancer, and reported frequencies of 31.4 % -32.4 % for all polyps [24,25] and 0.7 % -1.5 % for adenocarcinomas [6 -99. This contradiction may be explained by the fact that male sex, more advanced age (≥ 62 years), and a diagnosis of early gastric cancer were found to be the greatest risk factors for synchronous or metachronous colorectal adenocarcinoma in previous studies [6,7,24].…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Most secondary colorectal cancers develop within 3 years of the initial diagnosis, and, since a portion of them steadily develop for 5 years after detection of primary gastric cancer [4,6], screening FCS should be performed for at least 5 years after endoscopic removal of gastric lesions. Meanwhile, the prevalence of overall colorectal polyps and of colorectal adenocarcinomas seen in this study is higher than that observed by previous studies which dealt with the prevalence of colorectal neoplasms in patients with gastric cancer, and reported frequencies of 31.4 % -32.4 % for all polyps [24,25] and 0.7 % -1.5 % for adenocarcinomas [6 -99. This contradiction may be explained by the fact that male sex, more advanced age (≥ 62 years), and a diagnosis of early gastric cancer were found to be the greatest risk factors for synchronous or metachronous colorectal adenocarcinoma in previous studies [6,7,24].…”
Section: Discussioncontrasting
confidence: 80%
“…Meanwhile, the prevalence of overall colorectal polyps and of colorectal adenocarcinomas seen in this study is higher than that observed by previous studies which dealt with the prevalence of colorectal neoplasms in patients with gastric cancer, and reported frequencies of 31.4 % -32.4 % for all polyps [24,25] and 0.7 % -1.5 % for adenocarcinomas [6 -99. This contradiction may be explained by the fact that male sex, more advanced age (≥ 62 years), and a diagnosis of early gastric cancer were found to be the greatest risk factors for synchronous or metachronous colorectal adenocarcinoma in previous studies [6,7,24]. These findings also underline the need for routine FCS in patients with gastric adenomas or early cancers treated with EMR or ESD.…”
Section: Discussioncontrasting
confidence: 80%